Peningkatan Keterampilan Berbahasa Inggris Guru Sekolah Dasar dalam Mempublikasikan Budaya Melayu Riau melalui Googleclassroom: Penguatan Keterampilan Berbahasa dalam Mempublikasikan Budaya Melayu Riau - Marhamah, Marhamah; Yuliani, Sri; Nurmalinda, Nurmalinda; Kumalasari, Cyintia; Samsudin, Dafrizal; Fahrezi, Mhd Ryan; Sumardi, Sumardi (Berdikari: Jurnal Inovasi dan Penerapan Ipteks, 2025)
This Community Service (PkM) activity intends to enhance the comprehension and foster teachers’ creativity and competence. Teachers require comprehensive support in English instruction, utilizing textbooks that offer contextual learning to address diverse needs and learning styles. The Emancipated Curriculum grants teachers with greater freedom in designing and executing learning processes that cater to student needs, highlighting a flexible and student-centered methodology. The PkM team organized an activity to promote Riau Malay culture via social media. This activity employed a methodical approach consisting of several stages: first, the introduction and utilization of integrated textbooks on Riau Malay culture; second, the enhancement of English language skills for the promotion of Riau Malay culture; and third, the evaluation process. The research findings indicate a notable enhancement in teachers' English language proficiency, achieving scores of 4 or 5 (High), particularly in the aspect of writing and speaking, which are interwoven with local cultural knowledge. This demonstrates a significant accomplishment of a primary objective, specifically the enhancement of teacher competence. Google Classroom has demonstrated efficacy as a platform for collaboration and the dissemination of Malay cultural materials in English. This research suggests the development of more proficient teachers capable of enhancing regional cultural diversity for a broader audience via digital technology, while also boosting students’ motivation through pertinent and engaging material